Elevating Antioxidant Profiling of Medical Plant: Integration of Experimental Assays with Extensive in Silico Analyses for Comprehensive Evaluation - Ahmim Souhila; Allali Donia; Zegueb Ikram (Université of Eloued, 2025)
This work is part of a research programme in medicinal plants, where research was conducted on two types of plants: cotula cinerea and Origanum Majorana L. , the essential oil for which was derived and analysed by the gas chromatography linked to the mass spectrometer (GC/MS) to identify its components. The results showed the enrichment of plants under study with base oils, with a variation in the number and type of vehicles for the first type (cotula cinerea), which is growing particularly in the desert regions of the Arab region. The second type that is particularly developing around the Mediterranean regions is the origin of Origanum Majorana L with 42 known compounds and its main compound being trans thujone (33.3%). Anti-oxidation effectiveness was also determined using the DPPH test, where it was found through the results that all the extracts had an anti-oxidant effectiveness, but compared to vitamin E, which was considered weak. By comparing the median concentration values of IC50, the resulting compounds showed that vitamin E was the most powerful anti-oxidant activity.
Keywords: Bioefficiency (antioxidative); Cotula cinerea; Origanum Majorana L; IC50; DPPH; الفعاليةالحيوية Citation